Does E-Voting matter for turnout, and to whom?. (June 2021) - Petitpas, Adrien; Jaquet, Julien M.; Sciarini, Pascal
Abstract: Empirical evidence suggests that e-voting has no measurable effects on turnout. However, existing studies did (or could) not look at e-voting effects on the individual level. We innovate by analyzing whether and to what extent the availability of e-voting fosters turnout among specific groups of citizens, and how this influences the equality of participation. To that end, we estimate Bayesian multi-level models on a unique set of official data on citizens' participation covering 30 ballots between 2008 and 2016 in Geneva, Switzerland, which has the most far-reaching experience with e-voting worldwide. Despite the fact that e-voting was added to an easy-to-use form of postal voting, we find that offering e-voting has increased turnout among abstainers and occasional voters. By contrast, the effects of e-voting availability on the equality of participation are mixed with respect to the age cohorts and gender.